COMPARATIVE ANALYSIS OF THE CONCEPTS OF «COMPETITIVE STABILITY» AND «COMPETITIVENESS» OF SERVICE ORGANIZATIONS - D. V. Akopyan; I. A. Suvorov (Вестник университета, 2019)
A comparative analysis of the categories, that form the concepts of competitiveness and competitive stability in relation to the organization of the services sector, has been conducted. The main approaches to the definition of categories and concepts, such as «competitive position», «competitive status», «competitive potential», «competitive advantages» have been analyzed. Their clarifications regarding the organizations of the service sector have been made. Based on the conducted comparative analysis, the concept of competitive advantages has been formulated as a basis for the formation of competitiveness and potential competitive stability of the organization of the services sector.